2017
DOI: 10.3390/atoms5030026
|View full text |Cite
|
Sign up to set email alerts
|

Stark Widths of Ar II Spectral Lines in the Atmospheres of Subdwarf B Stars

Abstract: Stark broadening parameters are of interest for many problems in astrophysics and laboratory plasmas investigation. Ar II spectral lines are observed in many kinds of stellar atmospheres such as the atmospheres of B-Type stars and subdwarf B stars. In this work, we present theoretical Stark widths for Ar II spectral lines. We use the impact semiclassical perturbation approach. Our results are compared with the available experimental values. Finally, the importance of the Stark broadening mechanism is studied i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 25 publications
2
11
0
Order By: Relevance
“…For example, the agreement with Djurović et al (2013) was 27% for 4p-4d transitions except for four transitions. Concerning Stark widths, the comparison with experiments is made in Hamdi et al (2017Hamdi et al ( , 2018 for 212 spectral lines and we found an agreement generally good. For example, the average agreement for 4p-4d transitions was 10% comparing with Djurović et al (2013) and 20% comparing with Pellerin et al (1997).…”
Section: Resultssupporting
confidence: 68%
“…For example, the agreement with Djurović et al (2013) was 27% for 4p-4d transitions except for four transitions. Concerning Stark widths, the comparison with experiments is made in Hamdi et al (2017Hamdi et al ( , 2018 for 212 spectral lines and we found an agreement generally good. For example, the average agreement for 4p-4d transitions was 10% comparing with Djurović et al (2013) and 20% comparing with Pellerin et al (1997).…”
Section: Resultssupporting
confidence: 68%
“…We compare our results (Q and SCP SST ) to the SCP calculations (SCP BD ) performed in [12], where atomic data have been taken from the method of Bates and Damgaard [13]. This method has been used many times with different ions, and it has been shown that the corresponding results (using the Bates and Damgaard or the SST data) are in good agreement with experimental and other theoretical results [31][32][33]. Many of these SCP results have been stored in the database STARK-B [34].…”
Section: Line Broadening Resultsmentioning
confidence: 60%
“…In order to introduce corrections to the widths and shifts due to the difference between calculated and experimental wavelengths, equation ( 8) of Hamdi et al (2013) has been used. Previously, we have checked the accuracy of our method by comparing our results with experimental data (Hamdi et al 2017(Hamdi et al , 2018(Hamdi et al , 2019.…”
Section: The Methodsmentioning
confidence: 99%